Hierarchical nano-branched c-Si/SnO2 nanowires for high areal capacity and stable lithium-ion battery. (January 2016) - Song, Hucheng; Wang, Hong Xiang; Lin, Zixia; YU, Linwei; Jiang, Xiaofan; Yu, Zhongwei; XU, Jun; Pan, Lijia; Zheng, Mingbo; Shi, Yi; Chen, Kunji
Abstract: Hierarchical structures, with a high mass-loading of nanostructured lithium (Li) storage medium grafted upon large trunk framework, represent a novel approach towards high capacity and stable Li-ion batteries. We here report a new hierarchical structure of crystalline Si nanowires (c-Si NWs) grafted upon ultra-long tin dioxide (SnO2 ) NW trunks, where the latter frame up a large, conductive and stable architecture (i) to achieve a high mass-loading of c-Si NWs for Li-ion storage and (ii) to guarantee a good electric contact and fast charging process. The Si NWs branches are produced via a low-temperature vapor-liquid-solid (VLS) growth catalyzed by Sn droplets produced during a simple H2 plasma treatment upon the SnO2 trunks. Compared to other Si or SnO2 NW-based anodes structures, the c-Si/SnO2 NWs hierarchical structure demonstrates an outstanding performance with a high mass-load (~1.5 mg/cm 2 ) and a high areal capacity (~1.8 mAh/cm 2 ) after 100 cycles, without the use of any additional conductive polymer binder, highlighting the unique synergistic benefit of this hierarchical structure in boosting simultaneously the capacity and stability of Si-loaded Li-ion batteries. Graphical abstract: Highlights: A hybrid hierarchical structure of Si nanowires (NWs) grafted upon SnO2 NWs trunks. Boosting both the specific capacity (3400 mAh/g) and the stability of Si-loaded LIBs. With a high mass-load ~1.5 mg/cm 2 and record-high areal capacity of 1.8 mAh/cm 2 .